The road map from plough to plate - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
What goes into people's food, whether on your own plate or your customer's 10,000 km away, has become a hot issue in health, nutrition and international trade. There's much more to food safety than additives (see Food Additives article). An introduction t